2010
DOI: 10.5194/hess-14-1417-2010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intra-country virtual water trade strategy to alleviate water scarcity in Iran

Abstract: Abstract. Increasing water scarcity has posed a major constraint to sustain food production in many parts of the world. To study the situation at the regional level, we took Iran as an example and analyzed how an intra-country "virtual water trade strategy" (VWTS) may help improve cereal production as well as alleviate the water scarcity problem. This strategy calls, in part, for the adjustment of the structure of cropping pattern (ASCP) and interregional food trade where crop yield and crop water productivity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…In general, in the downstream of Kangsabati dam, the model prediction has larger uncertainties. The poor calibration and validation results in case of managed downstream flow has also been observed in other studies (Faramarzi et al, 2010;Vaghefi et al, 2013) (Fig. 1).…”
Section: Swat Model Calibration and Validationsupporting
confidence: 63%
“…In general, in the downstream of Kangsabati dam, the model prediction has larger uncertainties. The poor calibration and validation results in case of managed downstream flow has also been observed in other studies (Faramarzi et al, 2010;Vaghefi et al, 2013) (Fig. 1).…”
Section: Swat Model Calibration and Validationsupporting
confidence: 63%
“…While previous analyses (with the exception of a few national case studies, e.g., Faramarzi et al, 2010;Verma et al, 2009;Ma et al, 2006) addressed virtual water flows only between countries, our novel approach identifies globally at grid cell level (5 arcmin resolution) crop production surpluses relative to local demand and from that potential export grid cells. By combining those with grid cell specific crop-water use and bi-national trade data, we determine detailed flows of primary crop commodities and associated virtual water within and between countries ( Fig.…”
Section: Calculation Of Crop Commodity and Virtual Water Flows And Comentioning
confidence: 99%
“…To date, virtual water trade has not been evaluated thoroughly for Iran, primarily due to lack of data. The exception is the study by Faramarzi et al (2010) [35], who designed five scenarios to assess how virtual water trade may help to improve cereal production in Iran. They concluded that most of the current water transfer projects in Iran, specifically implemented for wheat production, are not efficient.…”
Section: Introductionmentioning
confidence: 99%